UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MENERAPKAN PENDEKATAN PEMBELAJARAN TEMATIK MELALUI SUPERVISI AKADEMIK SDN 18 KAMPUNG PANSUR (SEKOLAH BINAAN) - Syafruddin, Syafruddin (Jurnal Manajemen Pendidikan, 2019)
The problems that occurred at SDN 18 Kampung Pansur were from 3 teachers who taught in grades 1,2 and 3, only about 35% were of good quality in applying thematic learning approaches, the rest were 65% who taught grades 1,2 and 3 including in qualifications the value is lacking in applying thematic learning approaches. For this reason, with school action research through academic supervision, there can be at least some solutions / efforts to improve the ability of teachers to implement thematic learning approaches at SDN 18 in Kampung Pansur. With research procedures (PTS), namely through planning, action, observation and reflection in cycle 1, there is a significant increase in the cycle 2 action. Based on the results of the implementation of the study shows that the implementation of the first cycle obtains a change in the increase in significant results in the second cycle. of the 3 teachers in grades 1,2, and 3 who previously qualified for less in applying the thematic learning approach, now 29% have qualified enough and 30% have good grades. This means that through this study there is an increase of around 30% overall .